2018
DOI: 10.1590/2179-8087.065917
|View full text |Cite
|
Sign up to set email alerts
|

Water Flow Evaluation in Eucalyptus and Corymbia Short Logs

Abstract: The aim of this study is to evaluate the free and adsorbed water flow in short logs of Eucalyptus urophylla and Corymbia citriodora clones. 40 cm long, short logs were extracted from the base of the trees. Three trees each of C. citriodora and E. urophylla (A and B clones) were used. 27 logs were debarked and dried to achieve stabilization of mass. Free water (FWFR), adsorbed water (AWFR) and total water (TWFR) flow rates, and basic density were calculated. FWFR was greater than TWFR, which was superior to AWF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…The mean basic density of Corymbia citriodora wood equal to 647 kg/m 3 (Table 1) is consistent with the literature, for example, Zanuncio et al (2015) found values between 665 and 684 kg/m 3 for Corymbia citriodora wood from seven-years-old trees, and Monteiro et al (2018) report mean values of basic density for trees of the same species and age equal to 610 kg/m 3 . The comparison with the values of water flow in wood is more complex since few studies approach the rates of the free and absorbed water in a detailed way, as well as diverse methodologies, are used for measure permeability, for example, apparatus for testing the permeability to air and liquid in wood (Silva et al 2010, Tanaka et al 2010, Baraúna et al 2014, Rezende et al 2018, Brito et al 2019 and gravimetric techniques (Redman et al 2016, Thybring et al 2018.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The mean basic density of Corymbia citriodora wood equal to 647 kg/m 3 (Table 1) is consistent with the literature, for example, Zanuncio et al (2015) found values between 665 and 684 kg/m 3 for Corymbia citriodora wood from seven-years-old trees, and Monteiro et al (2018) report mean values of basic density for trees of the same species and age equal to 610 kg/m 3 . The comparison with the values of water flow in wood is more complex since few studies approach the rates of the free and absorbed water in a detailed way, as well as diverse methodologies, are used for measure permeability, for example, apparatus for testing the permeability to air and liquid in wood (Silva et al 2010, Tanaka et al 2010, Baraúna et al 2014, Rezende et al 2018, Brito et al 2019 and gravimetric techniques (Redman et al 2016, Thybring et al 2018.…”
Section: Resultssupporting
confidence: 88%
“…Logs with 0,4m length, 17,88cm diameter and dried between 70,3 and 14,8% of moisture content obtained the following drying rates: 0,37; 0,72; and 0,17%MC day -1 for total drying, free water outlet (between 70,3 and 30%), and bound water outlet (between 30 and 14,8%), respectively (Monteiro et al 2018). The lower values of the total drying rate (TWFR) of Monteiro et al (2018) can be explained by their use of pieces of wood (Corymbia citriodora logs) with larger dimensions when compared to the specimens used in this study. Bramhall (1971) reports that wood permeability decreases as sample length increases.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Duarte et al (2015) encontraram valores de taxa de secagem superiores em média de 7,5 vezes maior na retirada da água capilar para Eucalyptus spp., enquanto que Santos et al (2003), encontraram taxa de secagem inferior de 4,6 vezes maior na retirada da água capilar durante a secagem da madeira de Eucalyptus grandis. A retirada da água livre por capilaridade apresenta maior taxa de secagem quando comparada com a água de impregnação ligada na parede celular (Klitzke e Batista, 2010;Monteiro et al, 2018;Nascimento et al, 2019), a qual é retirada por difusão, e que as características da madeira e o aproveitamento das condições climáticas irão influenciar na taxa de secagem (Santos et al, 2003;Klitzke e Batista, 2010). Para espécies do gênero Eucalyptus esse movimento de difusão sofre restrições pelas características anatômicas da espécie (Monteiro et al, 2017), com predomínio de pontuações de pequenos diâmetros e com vasos usualmente bloqueados por tilose, tornando a madeira impermeável (Vermaas, 2000).…”
Section: Taxa De Secagemunclassified